Challenges and burden of the Coronavirus 2019 (COVID-19) pandemic for child and adolescent mental health: a narrative review to highlight clinical and research needs in the acute phase and the long return to normality - Jörg M. Fegert; Benedetto Vitiello; Paul L. Plener; Vera Clemens (BMC, 2020)
Abstract Background The coronavirus disease 2019 (COVID-19) is profoundly affecting life around the globe. Isolation, contact restrictions and economic shutdown impose a complete change to the psychosocial environment in affected countries. These measures have the potential to threaten the mental health of children and adolescents significantly. Even though the current crisis can bring with it opportunities for personal growth and family cohesion, disadvantages may outweigh these benefits. Anxiety, lack of peer contact and reduced opportunities for stress regulation are main concerns. Another main threat is an increased risk for parental mental illness, domestic violence and child maltreatment. Especially for children and adolescents with special needs or disadvantages, such as disabilities, trauma experiences, already existing mental health problems, migrant background and low socioeconomic status, this may be a particularly challenging time. To maintain regular and emergency child and adolescent psychiatric treatment during the pandemic is a major challenge but is necessary for limiting long-term consequences for the mental health of children and adolescents. Urgent research questions comprise understanding the mental health effects of social distancing and economic pressure, identifying risk and resilience factors, and preventing long-term consequences, including-but not restricted to-child maltreatment. The efficacy of telepsychiatry is another highly relevant issue is to evaluate the efficacy of telehealth and perfect its applications to child and adolescent psychiatry. Conclusion There are numerous mental health threats associated with the current pandemic and subsequent restrictions. Child and adolescent psychiatrists must ensure continuity of care during all phases of the pandemic. COVID-19-associated mental health risks will disproportionately hit children and adolescents who are already disadvantaged and marginalized. Research is needed to assess the implications of policies enacted to contain the pandemic on mental health of children and adolescents, and to estimate the risk/benefit ratio of measures such as home schooling, in order to be better prepared for future developments.